2007
DOI: 10.1155/2007/23864
|View full text |Cite
|
Sign up to set email alerts
|

EEG-Based Brain-Computer Interface for Tetraplegics

Abstract: Movement-disabled persons typically require a long practice time to learn how to use a brain-computer interface (BCI). Our aim was to develop a BCI which tetraplegic subjects could control only in 30 minutes. Six such subjects (level of injury C4-C5) operated a 6-channel EEG BCI. The task was to move a circle from the centre of the computer screen to its right or left side by attempting visually triggered right- or left-hand movements. During the training periods, the classifier was adapted to the user's EEG a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…The task familiarity and acclimatization to the environment are thus highly important to get efficient BCI performance. 9,67 In many research articles, an enhanced motor performance has been reported after the mental practice and adaptation to the experimental environment in comparison to the novices. 30 Therefore, the practicing of MI is a promising intervention and has been observed to have significant correlation in improvement of performance of motor execution in patients with all types of motor impairments as well as in sports.…”
Section: Motor Imagery and Brain-computer Interfacementioning
confidence: 99%
“…The task familiarity and acclimatization to the environment are thus highly important to get efficient BCI performance. 9,67 In many research articles, an enhanced motor performance has been reported after the mental practice and adaptation to the experimental environment in comparison to the novices. 30 Therefore, the practicing of MI is a promising intervention and has been observed to have significant correlation in improvement of performance of motor execution in patients with all types of motor impairments as well as in sports.…”
Section: Motor Imagery and Brain-computer Interfacementioning
confidence: 99%
“…Commonly, researchers measure EEG signals at many electrode locations of brain. For examples, they measure 19 electrodes [3], 32 electrodes [1], 41 electrodes [4] or more than it. And they extract features from the electrodes to be aware of thinking of a subject (Fig.…”
Section: Fig 2 Somatotopic Representation Of Body Partmentioning
confidence: 99%
“…Brain-Computer Interface (BCI) is an interface technique between human and computer which can help severely motor-disabled persons to communicate and control their environment [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BCI is a system for communication and control with thoughts [14]. It can help severely motor-disabled persons to communicate and control their environments through many applications [15][16][17][18]. BCI systems can substitute for the loss of normal neuromuscular outputs by enabling people to interact with their environment through brain signals rather than thought muscles [19].…”
Section: Introductionmentioning
confidence: 99%